Tloušťka vrstvy nervových vláken sítnice u dětských pacientů s glaukomem měřená skenovací laserovou polarimetrií - Hložánek, Martin (Univerzita Karlova, Ovocný trh 5, 116 36 Praha 1, http://cuni.cz/, 2016)
Martin Hložánek: Retinal nerve fiber layer thickness in pediatric glaucoma patients, measured by scanning laser polarimetry Abstract Introduction Glaucoma is the leading cause of irreversible blindness worldwide. It is characterized as progressive neuropathy of retinal ganglion cells. Diagnosis of glaucoma can be difficult and often requires several different investigations, performed repeatedly. Evaluation of thickness of retinal nerve fiber layer (RNFL) by scanning laser polarimetry (with GDxVCC machine) belongs to the most sensitive objective methods of glaucoma diagnostics and monitoring and it is also easy to perform. Importance of this method is even higher in children, as the performance of other diagnostic methods is difficult due to poor cooperation. Normative databases of machines providing objective measurement of RNFL thickness, including GDxVCC, don't comprise data of subjects younger 18 years. Methods The aims of our work were to assess normative values of RNFL parameters on GDxVCC in healthy children and to compare them with values of children diagnosed with glaucoma. We performed measurements of RNFL thickness and basic ophthalmological testings in 186 children of age 7-17 years. During our study there were published papers pointing the influence of atypical birefringence pattern (ABP) on...